KONTRIBUSI MINAT BACA PROSA FIKSI TERHADAP KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS XI SMA SUNGAI GERINGGING KABUPATEN PADANG PARIAMAN - Maiza, Refni Afnita; Abdurahman, Abdurahman; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2018)
ABSTRACTÂ This research aims to describe and analyze the contribution of interest in reading prose fiction to the skill of writing short stories in class XI students of SMA Negeri Sungai Geringging Kabupaten Padang Pariaman. This type of research is quantitative with correlation design. The population of this research is the students of grade XI of SMA Negeri Sungai Geringging which is registered in academic year 2018/2019. There are two research variables, namely the interest in reading prose fiction (independent variables) and short story writing skills (dependent variables). The data was collected by giving performance test of short story writing skill and reading proxies reading fictional interest. Based on data analysis, it can be concluded that the interest in reading fiction prose contributes to the writing skills of students' short stories by 8.79%.Â Kata kunci: kontribusi, minat baca prosa fiksi, keterampilan menulis, teks cerpenÂ